The Effect of Ozonation Process on Bromide-Containing Groundwaters in Bandung Area and Its Surroundings - Syafila, Mindriany; Sukandar, Sukandar; Haryanto, Eric (ITB Journal Publisher, LPPM ITB, 2012)
Disinfection process was applied as the last step of the water treatment to kill pathogenic bacteria in the water. However, according to several studies, the ozonation disinfection process could form undesired by-products. One of the by-products potentially affecting human life is bromate produced from bromide ionic-containing water. This study was carried out to examine the effect of raw water characteristics and pH on bromate formation. Also, the performance of bromate formation for a period of exposure time was analyzed. Raw waters taken from four different areas around Bandung were exposed to ozone introduced to a reactor with a flow rate of 2 L/min. The pH of the raw waters varied from 4, 7 to 10. The results show that there was no evidence of an initial bromide ion concentration, whereas a change in pH value gives a significantly different outcome. In acidic condition (pH of 4) the bromate formation tends to decrease, whereas when the pH value increases to a pH of 10, the bromate formation increases. Therefore, for drinking water with a neutral pH, when bromide ions are detected in the raw water, the drinking water may be toxic due to the presence of bromate.